What Helps to Make SMEs Successful in Global Markets? - ERDİLEK KARABAY, MELİSA (ELSEVIER SCIENCE BV, 2014)
As the globalization rises, small and medium-sized enterprises (SMEs) have a very important role of opening the local products/services to the international markets, as well as competing with multinational competitors in the local markets. There are some entrepreneurial, external and internal factors behind the success of SMEs through the globalization process. The purpose of this paper is to identify and associate the main factors that affect the success of globally succesful Turkish SMEs. The analysis based on the results of the structured survey conducted to a sample of SMEs registered and nominated to export awards by Small and Medium Enterprises Development Organization and Women Entrepreneurs Association of Turkey. (C) The Authors. 2014 Published by Elsevier Ltd.
Keywords: Key success factors; Global; SMEs; Entrepreneur; MEDIUM-SIZED ENTERPRISES; FAMILY BUSINESSES; STRATEGY; INTERNATIONALIZATION; CAPABILITIES; GROWTH